Synthetic exendin-4 disrupts responding to reward predictive incentive cues in male rats - Wakabayashi, Ken T.; Baindur, Ajay N.; Feja, Malte; Suarez, Mauricio; Chen, Karie; Bernosky-Smith, Kimberly; Bass, Caroline E. (Frontiers in Behavioral Neuroscience, 2024)
Synthetic exendin-4 (EX4, exenatide), is a GLP-1 receptor agonist used clinically to treat glycemia in Type-2 diabetes mellitus. EX4 also promotes weight loss and alters food reward-seeking behaviors in part due to activation of GLP-1 receptors in the mesolimbic dopamine system. Evidence suggests that GLP-1 receptor activity can directly attenuate cue-induced reward seeking. Here, we tested the effects of EX4 (0.6, 1.2, and 2.4 µg/kg, i.p.) on incentive cue (IC) responding, using a task where rats emit a nosepoke response during an intermittent reward-predictive IC to obtain a sucrose reward. EX4 dose-dependently attenuated responding to ICs and increased the latencies to respond to the IC and enter the sucrose reward cup. Moreover, EX4 dose-dependently decreased the total number of active port nosepokes for every cue presented. There was no effect of EX4 on the number of reward cup entries per reward earned, a related reward-seeking metric with similar locomotor demand. There was a dose-dependent interaction between the EX4 dose and session time on the responding to ICs and nosepoke response latency. The interaction indicated that effects of EX4 at the beginning and end of the session differed by the dose of EX4, suggesting dose-dependent pharmacokinetic effects. EX4 had no effect on free sucrose consumption behavior (i.e., total volume consumed, bout size, number of bouts) within the range of total sucrose volumes obtainable during the IC task ( 3.5 ml). However, when rats were given unrestricted access for 1 hr, where rats obtained much larger total volumes of sucrose ( 30 ml), we observed some dose-dependent EX4 effects on drinking behavior, including decreases in total volume consumed. Together, these findings suggest that activation of the GLP-1 receptor modulates the incentive properties of cues attributed with motivational significance.